2004
DOI: 10.1038/sj.cgt.7700767
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone releasing hormone plasmid supplementation, a potential treatment for cancer cachexia, does not increase tumor growth in nude mice

Abstract: Growth hormone releasing hormone (GHRH) is known to have multiple anabolic effects and immune-stimulatory effects. Previous studies suggest that treatment with anabolic hormones also has the potential to mitigate the deleterious effects of cancer cachexia in animals. We studied the effects of plasmid-mediated GHRH supplementation on tumor growth and the role of antitumor immune cells with two different human tumor cell lines, NCI-H358 human bronchioalveolar carcinoma and MDA-MB-468 human breast adenocarcinoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
8
1
Order By: Relevance
“…The finding in our study that ghrelin and anamorelin do not promote tumor growth, even in the presence of elevated GH and IGF-1, is consistent with findings from other studies evaluating GH-based therapies in tumor-bearing animals [9, 2326], as well as in formal carcinogenicity studies in tumor-free animals [27], as summarized below.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding in our study that ghrelin and anamorelin do not promote tumor growth, even in the presence of elevated GH and IGF-1, is consistent with findings from other studies evaluating GH-based therapies in tumor-bearing animals [9, 2326], as well as in formal carcinogenicity studies in tumor-free animals [27], as summarized below.…”
Section: Discussionsupporting
confidence: 92%
“…Ghrelin activity is thought to be mediated by both growth hormone (GH)-dependent and GH-independent mechanisms [8]. However, the short half-life (∼30 min), and parenteral administration requirement of ghrelin has limited its clinical usefulness, and interest has switched to the development of orally available ghrelin mimetics [911]. One of these, anamorelin (ONO-7643, formally known as RC-1291), is a GRLN receptor agonist currently in development for the treatment of non-small-cell lung cancer (NSCLC)-related anorexia and cachexia.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in our laboratory we designed new plasmid backbones (pAV0201 series) and synthetically produce them. Using optimized backbone plasmids, we obtained long-term transgene expression at physiologic levels in various mammals, including cows and dogs [Khan, A.S. et al, 2005a;Tone, C.M. et al, 2004].…”
Section: Plasmid Backbone (To Be or Not To Be Useful: Cpg In Dna Vaccmentioning
confidence: 99%
“…Similarly, GH has been reported to have no effect on the growth of human bronchoaveolar carcinoma and human breast adenocarcinoma (Khan et al 2005). GH increases anabolic activity, and some of its effects may also be mediated by increasing the immune response (Redelman et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a study of tumorbearing mice indicated that stimulation of the GH-insulinlike growth factor (IGF) axis did not promote tumor growth (Khan et al 2005). A clinical study of cancer patients indicated that administration of GH alone or in combination with INS led to bodyweight gain and increased upper arm muscle mass and strength (Berman et al 1999).…”
Section: Introductionmentioning
confidence: 99%